Prediction of building envelope performance in the design stage:: an application for office buildings - Ünver, R; Akdag, NY; Gedik, GZ; Öztürk, LD; Karabiber, Z (PERGAMON-ELSEVIER SCIENCE LTD, 2004)
Building envelope should provide visual, thermal and acoustical comfort in accordance with the function of the room. The material properties of the translucent-window- and opaque components-wall- of the building envelope and the ratio of these components are effective in the establishment of comfort conditions in an interior. The perfection of the building envelope design is highly related to the consideration of all parameters together for visual, thermal and acoustical comfort. In this article, at first basic design process to predict the building envelope providing visual, thermal and acoustical comfort, namely optimum building envelope is explained, then the used methodologies and some of the results of a research project named Optimum building envelope design in terms of visual, thermal and acoustical comfort in offices are presented. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: building envelope; office; heat; sound; light; Construction & Building Technology; Engineering